CRITICAL DISCOURSE ANALYSIS ON LINGUISTIC IDEOLOGY USED ON BILLBOARDS IN JAKARTA - Dery Rovino; Theresia Arianti (Universitas Bunda Mulia, 2021)
ABSTRACTIndonesian language has long been officially determined as the national language of Indonesia. However, numerous texts in mass media embed English in the text being delivered. Previous studies have shown that English has long been used in Indonesia’s different media and platforms to, one of which, enhance the sense of prestige as well as class of the discourse presented. Though some researchers have conducted studies regarding the surface ideation of advertisements, little is known about the linguistic ideology behind the use of English in those texts, wherein the gap is fulfilled by the present study. This study aimed to analyze the linguistic ideology behind the English used on local billboards, with TACO framework. The findings showed that English is often used on local billboards in plenty of non-normative lexical positioning, unconventional spelling, and preferences in source language over the prescribed Bahasa Indonesia loan words. Study also found different modes of Bahasa Indonesia-English coinage as well as some evidence of disconnect between the Bahasa Indonesia-English use of expressions and the actual sold products. This study believes that these eccentric language pairings between Bahasa Indonesia and English lend themselves into the present ideology of prestige enhancement of the product and service advertised. This ideation is derived from a particular narrative that English is superior towards the national language, Indonesian language. Findings also exhibited that economic and education gaps are two main issues hidden behind the use of English on local billboards.